Perfusion Patterns of Ischemic Stroke on Computed Tomography Perfusion - Lin, Longting (Korean Stroke Society, 2013)
CT perfusion (CTP) has been applied increasingly in research of ischemic stroke. However, in clinical practice, it is still a relatively new technology. For neurologists and radiologists, the challenge is to interpret CTP results properly in the context of the clinical presentation. In this article, we will illustrate common CTP patterns in acute ischemic stroke using a case-based approach. The aim is to get clinicians more familiar with the information provided by CTP with a view towards inspiring them to incorporate CTP in their routine imaging workup of acute stroke patients.